Ley y negociación colectiva sobre jubilación en España - Elorza Guerrero, Fernando (2015)
The process of legislative reform driven in Spain since 2010 within the framework of the economic crisis that is plaguing the country, has touched in a significant effect on the legal regime of the retirement. Institution which is not outside to the reform of the legal regime of collective bargaining, which, in parallel, has been practiced in these years. In this sense, the adoption of legislative measures in favor of the prolongation of the active life of the workers and the increase in retirement age, has coincided in time with the promotion of legal enterprise collective bargaining, by declaring its applicative preference. To analyze these issues is dedicated this article, in which, on the other hand, it highlights the lack of a credible legislative action in favor of the development of complementary social protection in the area of retirement.